Gambaran Tingkat Pengetahuan tentang Pertolongan Pertama pada Kecelakaan pada Siswa Kelas X di SMK Bhakti Bangsa - Ningrum, Anggriani Indah Puspita; Sumrahadi, Sumrahadi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Injuries remain one of the leading causes of death globally, with over 5.8 million cases reported annually, particularly in developing countries. In Indonesia, the 2013 Basic Health Research (Riskesdas) data indicate a high incidence of school-related accidents, with the most common types of injuries being abrasions or bruises (70.9%), sprains (27.5%), lacerations (23.2%), and fractures. Muhammad and Nugroho (2024) also reported that other conditions such as choking, fainting, nosebleeds, poisoning, fever, and headaches are frequently experienced by students. These findings highlight the critical importance of knowledge and skills in first aid within school environments as an early intervention to prevent disability and mortality. Objective: This study aims to describe the characteristics of the respondents and to assess the level of first aid knowledge among tenth-grade students at SMK Bhakti Bangsa. Method: A quantitative descriptive research design was used, employing a total sampling technique involving 55 students. Results: The results showed that the majority of respondents had a good level of knowledge, with 51 students (92.7%) categorized as having good knowledge and 4 students (7.3%) categorized as having moderate knowledge. Conclusion: Most tenth-grade students at SMK Bhakti Bangsa demonstrated a good level of knowledge regarding first aid for accidents. This level of understanding was influenced by students’ previous participation in training sessions and information obtained through educational learning activities.